Comparative Analysis of Friction Stir Welding and Laser Welding - Ollikainen, Paavo (My University, 2025)
Various welding processes are used in manufacturing. Most recently invented processes try to improve on aspects such as productivity, and reduced metallurgical changes, and defects. The applicability of a welding process depends on factors such as base material compatibility, required equipment and energy efficiency. The objective of this thesis is to describe the fundamentals of two of the most prominent advanced welding processes, Friction-Stir Welding and Laser Beam Welding. This work is conducted as a literature review. Subjects which are studied of both processes include base materials compatibility, process parameters, energy efficiency, applications, advantages and limitations. Additionally, friction-stir welding is studied by the tools, heat transfer and material flow. For laser beam welding, laser sources and melt pool characteristics are studied. Key differences and similarities are discussed, and a summarizing table of these aspects is presented. In this study it is found that laser beam welding enables high productivity, whereas friction stir welding is limited on the welding speed and flexibility. It is found that, friction stir welding produces good quality welds with various aluminium alloys, whereas laser beam welding is best suited for low carbon steels, magnesium alloys and thermoplastics. Friction stir welding is suggested to be environmentally friendly with no use of consumables.
Keywords: Manufacturing, Joining, Friction-Stir Welding, Laser Welding